Capital Account Liberalization and Economic Performance : Survey and Synthesis - Sloek, Torsten (IMF Working Papers; Working Paper ;, 2002)
This paper reviews and discusses issues involved in assessing the relationship between capital account liberalization and economic performance. First, it discusses the different measures of restrictions used in the literature. Second, it reviews the literature on the relationship between growth and capital account liberalization. Finally, it identifies and explains some of the differences in the results of the various studies and provides some support for a positive effect of capital account liberalization on growth, especially for developing countries.